Sex differences in intellectual ability among preschool children in Putrajaya - Foong, Tang Lee; Arshat, Zarinah; Juhari, Rumaya (Global Academic Excellence, 2020)
Past research has shown that children with the higher intellectual ability or intelligence quotient (IQ) were found less likely to be held back a grade in their schooling years and were less likely to be rejected by their peers or to have very few friends. The present study was conducted to determine the sex differences in intellectual ability among preschool children in Putrajaya. The research sample of 234 preschool children aged 6 from 16 private preschools in Putrajaya Malaysia was selected by using a cluster sampling technique. Preschool children’s intellectual ability was measured by using The Drawing-A-Person Intellectual Ability Test for Children, Adolescents, and Adults (DAP: IQ; Reynolds & Hickman, 2004). Higher scoring on the DAP: IQ signified higher IQ level which represents the higher intellectual ability of the preschool children. Results showed that there was a significant difference in intellectual ability, where preschool girls were found to have higher intellectual ability scores than boys. The study concluded that preschool boys and girls were different in their biology and social development which may cause differences in their intellectual ability level. The finding implied the need for more attention from the preschool setting to further improve their academic planning in order to enhance both preschool boys and girl's learning and development.